Evaluation of a hydrophilic polymer in anaheim pepper (Capsicum annuum L.) cultivated in greenhouse - López-Elías, Jesús (REVISTA TERRA LATINOAMERICANA, 2013)
In order to improve water use efficiency in vegetable production, a hydrophilic polymer based on polyacrylamide (PAM) using drip irrigation in Anaheim pepper cv. Cardon under greenhouse conditions was evaluated. The experimental design was randomized complete blockd with five replications. The experimental unit was 4 m long, 1.5 m wide (6 m2) with 20 total plants and five for measurements. The parameters evaluated were fruits per plant, fruit weight, commercial yield, size (length and diameter), volume of water applied, water use efficiency (WUE) and chlorophyll content. The incorporation of the hydrophilic polymer had no positive effect on production, fruit quality, or WUE; however, there was an effect on the volume of applied water and chlorophyll content. With the polymer a yield of 1.5 kg m-2 with 24.9 fruits m-2, a fruit weight of 59.2 g, 16.2 cm length, 3.9 cm diameter, and WUE of 5 kg m3 were obtained, whereas in the control without polymer the yield was 1.7 kg m-2, with 26.7 fruits m-2, fruit weight of 62.1 g, 16.3 cm length, 4 cm diameter, and WUE of 4.9 kg m-3. With the incorporation of the polymer a 1.5% increase in soil moisture content was obtained, which represents a 12% reduction in the volume of water applied and a SPAD reading of 58.4 versus 57.7 of the control. Therefore, the use of hydrophilic polymer may be an important practice for producers who are required to apply less frequent irrigation and to reduce watering time.